2016
DOI: 10.1021/acs.bioconjchem.6b00209
|View full text |Cite
|
Sign up to set email alerts
|

A Helix-Stabilizing Linker Improves Subcutaneous Bioavailability of a Helical Peptide Independent of Linker Lipophilicity

Abstract: Stabilized peptides address several limitations to peptide-based imaging agents and therapeutics such as poor stability and low affinity due to conformational flexibility. There is also active research in developing these compounds for intracellular drug targeting, and significant efforts have been invested to determine the effects of helix stabilization on intracellular delivery. However, much less is known about the impact on other pharmacokinetic parameters such as plasma clearance and bioavailability. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…This was unexpected, as the addition of Cy5 to the lead i, i + 4 and i, i + 7 sequences ( 24 and 25 , respectively), did not elicit the same increase in helicity (Figure ). It has been reported that cyanine dyes can increase the helicity of peptide sequences, possibly due to the lipophilic structure of the dye interacting with side chains . It is also worth noting that compounds 23–25 do not have the characteristic maxima below 200 nm that is expected of an α‐helix.…”
Section: Resultsmentioning
confidence: 99%
“…This was unexpected, as the addition of Cy5 to the lead i, i + 4 and i, i + 7 sequences ( 24 and 25 , respectively), did not elicit the same increase in helicity (Figure ). It has been reported that cyanine dyes can increase the helicity of peptide sequences, possibly due to the lipophilic structure of the dye interacting with side chains . It is also worth noting that compounds 23–25 do not have the characteristic maxima below 200 nm that is expected of an α‐helix.…”
Section: Resultsmentioning
confidence: 99%
“…All chemicals were purchased from Sigma Aldrich, unless otherwise specified. Peptide and reaction details are provided in Supplemental Figure 1 (supplemental materials are available at http://jnm.snmjournals.org) (16,22). All animal experiments were conducted under the approval of the Institutional Animal Care and Use Committee at the University of Michigan and Memorial Sloan Kettering Cancer Center and followed the National Institutes of Health guidelines for animal welfare.…”
Section: Methodsmentioning
confidence: 99%
“…After purification, conjugates were run on SDS-PAGE and scanned on an Odyssey CLx to ensure all free dye was removed (Figure S2). Binding affinities were performed as previously described 3 using HCC1954 cells. Briefly, titrations of unlabeled antibody and antibody–dye conjugates were incubated with 50,000 HCC1954 cells on ice for 3 h and washed.…”
Section: Methodsmentioning
confidence: 99%